Atrioventricular block in acute coronary syndrome: Portuguese experience. (24th May 2021) - Santos, H; Santos, M; Almeida, I; Miranda, H; Sa, C; Chin, J; Almeida, S; Sousa, C; Almeida, L
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: Portuguese Registry of Acute Coronary Syndromes Background: The atrioventricular block (AVB) occurrence in acute coronary syndrome (ACS) is a potentially life-threatening complication, that demand a rapid and efficient response regarding reperfusion time and rhythm stabilization. Objective: Evaluate the impact and prognosis of AVB in ACS patients, as well as predictors of AVB. Methods: Multicenter retrospective study, based on the Portuguese Registry of ACS between 1/10/2010-3/05/2020. Patients were divided into two groups: A – patients without AVB, and B – patients that presented AVB. Were excluded patients without a previous cardiovascular history or clinical data regarding AVB occurrence. Logistic regression was performed to assess predictors of AVB in ACS patients. Results: From 32157 patients, 23774 was included, 23148 in group A (97.4%) and 626 in group B (2.6%). Both groups were similar regarding initial symptons until first medical contact (p = 0.410), smoker status (p = 0.222), arterial hypertension (p = 0.776), diabetes mellitus (p = 0.508), peripheral artery disease (p = 0.479), chronic kidney disease (p = 0.467) and re-infarction during the hospitalization for ACS (p = 0.145). Group A had higher body mass index (27.4 ± 4.4 vs 26.9 ± 4.6, p = 0.005), dislipidaemia (59.6 vs 51.4%, p < 0.001), coronary artery disease (18.9 vs 13.0, p < 0.001), heart rate (78 ± 19 vs 65 ± 25, p < 0.001), systolic blood pressure (139 ± 29 vs 119 ± 32, p < 0.001) and left ventricular ejection fraction (LVEF) >50% (60.1 vs 51.7%, p < 0.001). On the other hand, group B was elderly (66 ± 13 vs 71 ± 13, p < 0.001), female (27.4 vs 32.4%, p < 0.001), previous stroke (6.9 vs 10.9%, p < 0.001), neoplasia (4.9 vs 6.8%, p = 0.031), ST-segment elevation myocardial infarction (46.2 vs 75.4%, p < 0.001), syncope as major symptom (1.3 vs 10.0%, p < 0.001), Killip-Kimball class > I (15.4 vs 31.6%, p < 0.001), multivessel diasease (52.1 vs 61.4%, p < 0.001), heart failure complication (15.5 vs 40.6%, p < 0.001), cardiogenic shock complication (3.8 vs 24.6%, p < 0.001), new-onset of atrial fibrillation (4.2 vs 14.1%, p < 0.001), ACS mechanical complication (0.6 vs 3.2%, p < 0.001), sustained ventricular tachycardia during ACS hospitalization (1.3 vs 10.0%, p < 0.001), cardiac arrest (2.7 vs 13.3%, p < 0.001), stroke complication (0.6 vs 1.9%, p < 0.001) and hospitalization death (3.5 vs 19.0%, p < 0.001). Logistic regression revealed that female gender (odds ratio (OR) 1.422, p = 0.015, confidence interval (CI) 1.072-1.885), age ≥75 years old (OR 1.560, p = 0.002, CI 1.174-2.073), heart rate <60 (OR 6.692, p < 0.001, CI 5.180-8.644) and Killip-Kimball class > I (OR 3.264, p < 0.001, CI 2.446-5.356) were predictors of AVB in ACS patients. Conclusions: Female gender, age ≥75 years old, heart rate <60 and Killip-Kimball class > I were predictors of AVB in ACS patients.